La crise des vocations dans l'Espagne postconciliaire - Ruiz Andrés, Rafael (Archives de sciences sociales des religions, 2024)
After Franco's victory in the Civil War (1939), there was an explosion of religious vocations in Spain. However, between the end of the 1960s and the beginning of the 1970s, which was a period of economic development and of the impact of the post-conciliar process, the seminaries and novitiates were decimated by a crisis of religious vocations. Using historical sources, statistical records and qualitative fieldwork, this article explores both historical moments, the explosion of vocations and the crisis during the sixties, in order to analyse the causes of the emptying of seminaries and novitiates from the sixties onwards. For this purpose, the term "plausibility structure" is used to show that this drastic change was not only due to a sum of factors, but to a profound transformation that undermined the sociological foundations of some religious structures. As an epilogue, a reflection on the subsequent evolution of seminaries and novitiates is included, showing that what was experienced in the late sixties and early seventies was not a one-off crisis, but rather a structural crisis that continues to date, in an increasingly secularised and plural Spain.